Dynamic Effects of the Minimum Wage on Informality in Colombia (2017)
Informality is a common phenomenon in developing countries and is not uncommon in industrialized societies. Although persistent aggregate rates of informal employment for a certain period of time may be indicative of low rates of employment status change among individuals, more intensive studies regarding persistent individual informal employment are needed. We used a reduced-form dynamic pseudo panel data model approach that accounted for unobserved heterogeneity and initial conditions to present empirical evidence of the extent of persistent informality in a developing country, where education is the primary force of mitigating permanent informality. Using data from Colombia, we also provide results on the complex effect of minimum wage levels on informality. An increase in the minimum wage resulted in increased informality and increased the persistence of informality. Our results may be a basis with which to discuss the persistence of informality in other developing countries. © 2016 CEIS, Fondazione Giacomo Brodolini and John Wiley & Sons Ltd